Penyuluhan Cara Menghadapi Generasi Millenial Bekerjasama Dengan Sekolah, Gereja Dan Radio - Krishervina Rani LIDIAWATI (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
Internet has been widely used by children and teenager which could have an impact on child development. Therefore, information about parenting millennials that can’t be separated from the internet is needed. Parenting style plays a role in ensuring healthy development of children physically, cognitive, and psychosocial. Many children can’t stay away from gadget and that affect child’s emotion, behaviour, and even achievement at school which in turn overwhelmed their parent. This problem prompted community services in the form of public education for parents done through school, church, and radio. This community services collaborate with school, church and radio station. The first public education is done for parents of students in TK Budaya school. The second public education is done for parents and Sunday school teachers of Charismatic Worship Service (CWS) church at Senen, Jakarta. The third public education is done through collaboration with Yayasan Busur Emas (YBE) in their program “Parenting with Heart” that’s broadcasted through Heartline radio 100.6 FM. These programs are done in hope of wider dissemination of information so that more parents are able to face millenials who are fluent in using digital technologies. Based informal survey done on the public education at school and church, more than 50% of parents already knew the negative effect of excessive gadget usage but still don’t have rules on using gadget at home.